The next leap in productivity : what top managers really need to know about information technology - Kolawa, Adam (John Wiley & Sons, 2009)
How much should top management really care about IT' That's the question Adam Kolawa bluntly poses in this feisty and compelling book. "The Next Leap in Productivity" goes far beyond traditional business books written for the CIO community. It tackles crucial issues such as productivity, efficiency and quality management. It makes the case for applying the principles of Deming and Juran to software development. Then it takes a "leap," arguing that huge potential increases in IT productivity can lead to enormous increases in enterprise productivity. In this sense, "The Next Leap in Productivity" is a truly visionary book. Software vendors and CIOs who read this book will discover a software development process that is transparent, practical and efficient. Non-technical C-level executives (CEOs, CFOs, COOs, etc.) will discover a blueprint for improving corporate productivity and dramatically reducing operating costs. For the past decade, CIOs have been urged, coaxed, counseled and exhorted to act more like CEOs, CFOs, COOs and other C-level executives. This book suggests that it's time for CEOs, CFOs, COOs and other C-level executives to start acting more like CIOs. "The Next Leap in Productivity" will appeal to anyone involved in buying, selling, developing or using IT. bAdvance Praise for "The Next Leap in Productivity"/b "Adam's book is a challenge to all the top managers who've stopped caring about IT. His message is simple: If you really care about IT, you find ways to make IT more productive. The improvements you achieve in IT productivity can then be leveraged into huge leaps in productivity at the enterprise level. This book offers a roadmap for translating IT productivity into business profit. Adam's argument is worth reading and worth considering as you formulate your IT strategies and plan your IT budgets."--BGary Beach, Publisher Emeritus, CIO magazine/b "Adam lays the groundwork for a common language that can be used to bridge the chasms between IT and other essential components of the business such as finance, product development, sales, marketing, distribution and customer service. Everyone who reads this book will learn valuable lessons that can be leveraged to improve returns on human capital investments at every level of the organization. Adam's concepts have the potential to boost levels of confidence and performance throughout the enterprise."--bMichael Minelli, Co-author, Partnering with the CIO/b "These kinds of productivity principles are not mere theory. When we put these same principles into effect, our productivity went up more than we had thought possible. And our employee morale went up, too. It became easier to write code the right way and harder to make stupid mistakes. This new way of creating software makes it possible for us to concentrate on what we really want to do here at Cisco, which is to improve the Internet for everybody."--bAndy Chessin, Senior Technical Lead, Cisco, Inc./b